JUMLAH EMISI GAS CO2 DAN PEMILIHAN JENIS TANAMAN BERDAYA ROSOT SANGAT TINGGI: STUDI KASUS DI KOTA BOGOR (The Amount of CO2 Gasses Emission and Selection of Plant Species with Height Carbon Sink Capability: Case Study in Bogor Municipality) - Endes N. Dahlan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
Activities in towns and cities require energy from fossil fuel which can cause increasing concentration of CO2 ambient. One of the effort to minimize the increasing CO2 concentration in the atmosphere, particularly in the urban area, is to develop urban forest. The objective of the research is to measure the concentration of CO2 and to measure the ability of absorbing CO2 gas by urban forest trees in Bogor Botanical Garden and Forest Research Station at Dramaga. The result of the study noticed that: CO2 gas emission in 2015 is 452.486 ton, in 2095 will be 584.142 ton which can then induce increasing the concentration of CO2 ambient. The other research noticed that classification of absorption ability of trees in urban forest area which consist of Bogor Botanical Garden and Forest Research Station at Dramaga are as follow: very high consist of: F. benjamina, T. verrucossum, D. excelsum, C. odoratum (average absorption ability was 643,77 kg/trees/year), high absorption ability are: L. speciosa, A. pavoniana, C. parthenoxylon, S. mahagoni, P. pinnata, F. decipiens, B. roxburghiana (average was 305,91 kg/trees/year), moderate class are: S. wallichii, A. muricata, K. senegalensis, S. macrophylla, C. grandis, A. heterophyllus, T. grandis (average was 102,07 kg/trees/year), low class are: P. indicus, P. affinis, A. mangium, S. indicum, I. bijuga, K. anthotheca, D. retusa, C. pulcherrima, C. guinensis (average was 28,00 kg/trees/year) and very low class are: C. excelsa, H. mengarawan, T. indica, N. lappaceum, H. odorata, E. cristagalli, M. grandiflora, P. dulce (average was 3,90 kg/trees/year).Keywords: CO2, sequestration, urban forest, green open space